ATRT-37. TARGETING ATYPICAL TERATOID/RHABDOID TUMOR USING MATURE LET-7 LEADS TO INCREASED APOPTOSIS. Issue 2 (22nd June 2018) - Shahab, Shubin; Rubens, Jeffrey; Eberhart, Charles; Raabe, Eric
Abstract: Atypical teratoid rhabdoid tumors (AT/RT) are one of the most malignant brain tumors of childhood with very limited treatment options available. AT/RT tumors are characterized by INI1 (SMARCB1/BAF47/SNF5) loss. Deletions or mutations in INI1 is associated with upregulation of LIN28 which is a regulator of developmental timing and self-renewal. LIN28 is also a known regulator of let-7 family of miRNAs. Previously we have demonstrated that downregulation of LIN28 inhibits AT/RT growth and proliferation. Transfection of mature miRNA mimetic into CHLA-06 and BT37 AT/RT cells can achieve greater than 50% efficient transduction. We find increased apoptosis as measured by cleaved caspase 3 immunofluorescence using mature let -7g in BT37 and CHLA06 ATRT cells (14.5% and 5.3% increase; p value = 0.045 and 0.03 respectively). We are optimizing in vivo delivery strategies using nanoparticles to deliver mature let-7 g to AT/RT tumor cells in the brain. Such a strategy could be helpful to limit local recurrence of tumor and reduce the need for local radiation therapy in very young AT/RT patients.